Analisis Peran Fasilitas Pangkalan Korps Marinir dalam Mendukung Kesiapan Operasi - Maykel Indra Nandar; Abdul Kadir Mulku Zahari; Sikop Pauli Simangunsong (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the role of the Indonesian Marine Corps Base Facilities (Faslan Kormar) in supporting operational readiness and identify factors inhibiting its optimization. The research employs a qualitative approach with a case study design conducted within the Indonesian Marine Corps Headquarters. Data were collected through in-depth interviews with key personnel, observation, and documentation studies, then analyzed using thematic analysis. The findings indicate that Faslan Kormar plays a vital role as a strategic enabler through three main functions: development of construction facilities, management of transportation service facilities, and management of land facilities. However, the implementation of these roles faces four main constraints: (1) suboptimal organizational structure under the Logistics Staff; (2) lack of clear centralized development; (3) limitations in human resources and budget; and (4) complicated bureaucratic procedures. The impact of this suboptimal performance includes hindered soldier training processes, reduced unit mobility and maneuverability, and budget inefficiencies that ultimately decrease operational readiness. The study recommends organizational transformation of Faslan Kormar into an independent Base Facilities Service (Disfaslan Kormar), followed by function consolidation, human resource strengthening, and bureaucratic simplification to create an effective force multiplier for the Indonesian Marine Corps' operational readiness.